1993
DOI: 10.1063/1.354911
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of thermal residual stresses at graded ceramic-metal interfaces. Part II. Interface optimization for residual stress reduction

Abstract: An elastic-plastic finite element method numerical model previously developed (see Part I of this article) for predicting thermal residual stresses at graded ceramic-metal interfaces has been applied to determine interface conditions favorable for achieving residual stress reductions. Using Al2O3-Ni as a model system, and for a fixed specimen geometry, a study was performed to investigate the effects of different interlayer thicknesses and nonlinear composition profiles on strain and stress distributions estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(43 citation statements)
references
References 3 publications
1
42
0
Order By: Relevance
“…Drake et al The power distribution law was utilized to prove that significant stress and plastic strain reduction can be accomplished through increasing the ceramic materials thickness gradient and tailoring the exponent to create a compositional change gradient close to the parts showing high modulus and little plasticity [81]. Matsuo et al [82] fabricated functionally graded dental post (FGDP) using laser lithography, one of the photo-curing type computer-aided design/computer-aided manufacturing (CAD/ CAM).…”
Section: Dental Post Based On Functionally Graded Conceptmentioning
confidence: 99%
“…Drake et al The power distribution law was utilized to prove that significant stress and plastic strain reduction can be accomplished through increasing the ceramic materials thickness gradient and tailoring the exponent to create a compositional change gradient close to the parts showing high modulus and little plasticity [81]. Matsuo et al [82] fabricated functionally graded dental post (FGDP) using laser lithography, one of the photo-curing type computer-aided design/computer-aided manufacturing (CAD/ CAM).…”
Section: Dental Post Based On Functionally Graded Conceptmentioning
confidence: 99%
“…In order to estimate the elastic and plastic properties of the different composites used as interlayer a modified rule of mixtures (ROM) was used. This ROM works well for functionally graded materials [8][9][10]. Figure 7 shows a schematic representation of this ROM.…”
Section: 2mentioning
confidence: 99%
“…The value of q used in the current model, -4.5 GPa, was based on earlier work [8,9] for the elastic-plastic system Al 2 O 3 -Ni. Williamson et al showed that the stress is not very sensitive to changes in the transfer coefficient [8].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Later on the stress singularity at the interface of a composite can be eliminated and thus bonding strength enhanced. Studies show that, the thermal residual stresses can be drastically reduced by using FGM [11][12][13].…”
Section: Introductionmentioning
confidence: 99%